Occupational gender composition and wages in Romania: from planned equality to market inequality? - Daniela Andrén; Thomas Andrén (Institute for the Study of Labor (IZA), 2007)
In Romania, the communist regime promoted an official policy of gender equality for more than 40 years, providing equal access to education and employment, and restricting pay differentiation based on gender. After its fall in December 1989, the promotion of equal opportunities and treatment for women and men did not constitute a priority for any of the governments of the 1990s. Given that both the economic mechanisms and the institutional settings changed radically, the question is if this affected gender equality. This paper analyzes both gender and occupational wage gaps in Romania before and during the first years of transition from a planned to a market economy. The results suggest that the communist institutions did succeed in eliminating the gender wage differences in female- and male-dominated occupations, but not in gender-integrated occupations, for which the gender wage gap was about 32%. During the transitions years, this gap decreased to 20-24%, while the gender wag gap in male and female-dominated occupations increased to 15%.
Keywords: J24; 330; Occupational segregation; gender wage gap; occupational wage gap; Gleichberechtigung; Arbeitsmarktsegmentierung; Lohndifferenzierung; Frauenerwerbstätigkeit; Übergangswirtschaft; Rumänien